Seasonal Variation and Governing Dynamics of the Mixed Layer in the Indian Sector of the Southern Ocean. Issue 4 (4th April 2022) - Ferreira Azevedo, Matheus; Aoki, Shigeru; Kitade, Yujiro
Abstract: The dynamics involved in the variability of temperature, salinity, and density distributions in the upper layer of the Indo‐Pacific sector of the Southern Ocean were studied using Acoustic Doppler Current Profiler and Conductivity Temperature Depth data from a mini triangle trans‐ocean buoy network mooring deployed at 60°S and 140°E between January 15th and 19th December 2012, together with hydrographic casts, reanalysis outputs, and satellite imagery. Spectral analysis confirmed that near‐inertial internal waves are a major factor transporting energy downward to the lower boundary of the mixed layer (ML), with 12.5 J m −3 or 45% of the mean surface energy being able to reach deeper than the ML depth during one of the analyzed events. During a period of net heat loss from the ocean surface to the atmosphere, most of the energy was concentrated below the maximum shear layer, at around 80 m depth. Internal wave events were found to be linked to scalar diffusivity increases of up to two orders of magnitude. A box model clarified that surface cooling plays the most significant role in mixing surface waters during winter, but it is not enough to explain variability below 100 m depth, where horizontal advection and eddy enhancement are also important in modulating warm water flux. Our results elucidate how wind energy might enhance mixing, even in ice‐covered regions, while influencing depths greater than previously thought. Plain Language Summary: We compared temperature, salinity, and ocean‐current data recorded by a 2012 Antarctic expedition to satellite data and numerical models to determine the mechanisms behind the seasonal variation of these parameters in the Southern Ocean. Three main influencing factors were identified: Cooling of the ocean surface during winter, eddies, and near‐inertial internal waves. We found that internal waves are especially important for increasing mixing and their energy accumulates at around 80 m depth during winter. These results imply that wind might increase mixing, even in ice‐covered regions, and also reach deeper than previously thought. However, at layers deeper than 100 m from the ocean surface, the movement of underwater polar fronts, instigated by the strengthening of oceanic gyres, is essential for explaining variability, indicating a hidden underwater pathway guiding Antarctic waters during winter. Key Points: Net heat‐flux variability at the ocean surface is not sufficient to explain seasonal temperature variability below 100 m Seasonal variability of temperature and salinity below 150 m might be tied to strengthened warm‐core eddies Passage of near‐inertial internal waves enhanced mixing across the lower boundary of the mixed layer at the mooring location